Legal Analysis of Ownership Rights to Intangible Movable Property (Digital Assets) From the Perspective of Property Law In Indonesia - Kurdi; Muhammad Rizqi Alfarizi Ramadhan; Teuku Ahmad Dadek (Universitas Islam Negeri Alauddin Makassar, 2026)
The The rapid development of digital assets has posed fundamental challenges to Indonesia's property law system, which is still based on the colonial-era Civil Code (KUHPerdata). This legal system is inadequate to accommodate digital assets, resulting in legal vacuums and regulatory paradoxes. This study aims to analyze the status and regulation of digital asset ownership in Indonesia's property law system and the effectiveness of civil law protection for asset owners in ownership disputes. This research uses a normative approach by analyzing relevant legislation and legal doctrines. The results of the study show that there are legal loopholes and regulatory paradoxes in the regulation of digital asset ownership. The classification of digital assets as “intangible movable property” causes fatal incompatibilities in the process of transferring rights. Legal protection for digital asset owners is also illusory due to procedural paralysis. This study recommends a two-pronged reform, namely redefining the concept of “wealth” in the Draft Civil Code to include digital assets and drafting a lex specialis that regulates the procedural law of evidence and execution of digital assets. Thus, it is hoped that effective legal certainty can be created for digital asset owners in Indonesia.